Effects of whole-body electromyostimulation with different impulse intensity on blood pressure changes in hyper- and normotensive overweight people. A pilot study - Kemmler, Wolfgang; Kohl, Matthias; von Stengel, Simon; Willert, Sebastian; Kast, Stephanie; Uder, Michael (Frontiers in Physiology, 2024)
Hypertension is a frequent condition in untrained middle-aged to older adults, who form the core group of whole-body electromyostimulation (WB-EMS) applicants. So far, the acute effects of varying impulse intensities on blood pressure responses have not been evaluated in normo- and hypertensive people. Thirteen hypertensive and twelve normotensive overweight WB-EMS novices, 40-70 years old, conducted the same WB-EMS protocol (20 min, bipolar, 85Hz, 350µs, 4s impulse-4s rest; combined with easy movements) with increasing impulse intensity (low, moderate, advanced) per session. Mean arterial blood pressure (MAP) as determined by automatic sphygmomanometry rose significantly (p<.001) from rest, 5-min pre-WB-EMS to immediately pre-WB-EMS assessment. Of importance, a 20-min WB-EMS application does not increase MAP further. In detail, maximum individual MAP does not exceed 128 mmHG (177 mmHG systolic or 110 mmHG diastolic) in any case. Two-min post-WB-EMS, MAP was significantly lower (p=.016) compared to immediately pre-WB-EMS. In contrast, heart rate increased significantly from immediately pre to immediately post-exercise (p<.001), though individual peak values did not exceed 140 beats/min-1 and heart rate decreased rapidly (p<.001) post-exercise. No significant differences in MAP and HR kinetics were observed for impulse intensity categories or hypertensive status. In summary, largely independently of impulse intensity and status, the acute effect of WB-EMS on MAP in novice applicants seem to be largely negligible. Although definite evidence might not have been provided by the present study, we conclude that hypertension, at least under treatment, should not be considered as a barrier for WB-EMS application in moderately old or older cohorts.